Henry David Thoreau: his life, times, and literature - Cuenca O., Rocio; Lazo T., Mayra
HENRY DAVID THOREAU AND HIS LIFETIME This thesis concerns a study of Henry David Thoreau?s life and works. It has been divided into five chapters. The first chapter is about his biography, his friends and how his philosophy was incorporated in action. Thoreau belonged to the Transcendental Movement, where he established a relationship with other great thinkers. His philosophy, ?small is beautiful,? is one of the principles which he applied in his life. The second chapter refers to Walden and ?A Week on the Concord and Merrimack Rivers.? These works try to show us some of his theories about nature and its connection with men. Walden is considered one of his masterpieces due to its message to protect the surrounding world. ?A Week on the Concord and Merrimack Rivers? was dedicated to his adventures during a canoe-trip with his brother, John. The third chapter deals with an essay called ?Civil Disobedience,? where Thoreau expressed his dislikes against obeying government?s laws and paying taxes. The second point in this chapter is ?Life Without Principle,? where living a life without complications, spending our time on useful and constructive things, and enjoying our world, were the reasons which motivated Thoreau to write it. The fourth chapter has information about his influences from the nineteenth century to the presents. The impact that he has produced on our society is considerable, although at the very beginning he was not a well-known writer. The last chapter is the conclusion. It is the end of a deep analysis of Thoreau?s life and writings